Curcumin: Bioavailability and therapeutic potential in metabolic disorders and chronic diseases - Humaira Ashraf; Iahtisham-Ul-Haq; Seydi Yıkmış; Gholamreza Abdi; Rana Muhammad Aadil (Food and Humanity, 2026)

Molecular mechanisms in endometriosis: linking JAK/STAT pathway, ferroptosis, and microbial dysbiosis - Humaira Shah; Naguib Salleh; Mukhri Hamdan; Nelli Giribabu (Molecular Biology Reports, 2026)

PANI/CeO₂ nanocomposite membranes for efficient simulated textile dye wastewater treatment: A data-driven approach - Amna Siddique; Hafiza Hifza Nawaz; Humaira Razzaq; Muhammad Umar; Shumaila Razzaque; Anila Tabasum; Xuqing Liu; Muhammad Wakil Shahzad (Journal of Environmental Chemical Engineering, 2026)

Synergistic biochar/hydrogel composites: A next-generation platform for sustainable water treatment - Ankit Verma; Mukesh Kumar; Pooja Puri; Humaira Parveen; Sayeed Mukhtar; Mona O. Albalawi; Sangeeta Bhogal; Rohit Jasrotia (Journal of Environmental Chemical Engineering, 2026)

Exogenous hesperidin orchestrates antioxidant defense, osmolyte metabolism, and nutrient homeostasis to mitigate heavy metal toxicity in canola - Sherjeel Hashmat; Humaira Yasmeen; Bakhrom Jobborov; Muhammad Imran; Mohammed S. Alotaibi; Hossam S. El-Beltagi; Usman Zulfiqar; Amna Batool; Umer Farooq (BioMetals, 2026)

Fertilizing Effect of Codium flabellatum and Aspergillus japonicus (Algal-Fungal) Nexus Improves Growth, Nutrient Fluxes and Fruit Quality in Brassica napus in Saline Condition - Ayesha; Humaira Gul; Mamoona Rauf; Asma Tabassum; Aliya Rehman; Muhammad Arif; Muhammad Hamayun; Mohamed A. El-Sheikh; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2026)

Microbe-mediated drought stress alleviation: Fusarium verticillioides enhances maize growth by upregulation of physiological, biochemical, and molecular responses - Raid Ali; Humaira Gul; Mamoona Rauf; Sajid Ali; Muhammad Arif; Sumera Afzal Khan; Anwar Hussain; Bokyung Lee; Muhammad Hamayun (South African Journal of Botany, 2026)

Dual-loaded chitosan nanocarriers for sustainable management of Pseudomonas syringae in tomato: A critical narrative review and conceptual synthesis - Zeeshan Ahmad; Urooj Farid; Tauqeer Ahmed Qadri; Sana Azeem Kiani; Arslan Ali; Muhammad Nadeem Hassan; Humaira Yasmin (Physiological and Molecular Plant Pathology, 2026)

Nano-microbial suppression of Tribolium castaneum: Mortality, repellency, and enzyme responses to ginger-derived iron oxide nanoparticles and PGPR strains - Aneela Shaheen; Zeeshan Ahmad; Tauqeer Ahmed Qadri; Sidra Batool; Faheem Ahmad; Muhammad Nadeem Hassan; Humaira Yasmin (Journal of Stored Products Research, 2026)

Climate-adaptive strategies and nature-based solutions for emission control supporting environmental policy and sustainable mining decision-making - Humaira Yasmeen; Cheng Longsheng; Yasir Ahmed Solangi (Environmental Research, 2026)

A Fibrous Thin Film Based on Silver(I) Metal–Organic Framework/Polyethersulfone Composite with Excellent Antibacterial Properties and Photocatalytic Degradation of Methylene Blue - Humaira Shaheen; Abdul Rauf; Muhammad Arif; Muhammad Akram; Komal Aroosh; Mehdi Hassan; Muhammad Jahangir (Water, Air, & Soil Pollution, 2026)

Industrial pollution investment and climate risk: heterogeneous effects across the emission distribution - Humaira Yousafzai; Chen Jian (Theoretical and Applied Climatology, 2026)

Maximizing weight loss with cagrisema: a systematic review and GRADE-assessed meta-analysis of randomized controlled trials - Bilal Wazir Khan; Syed AsadUllah Agha; Ihsan Qamar; Muhammad Huzaifa Khattak; Amna Rehman; Tayyaba Ikram Qazi; Shahreena Athar Siddiqui; Nafila Zeeshan; Umer Zaryab Khan; Humaira Bibi; Muhammad Faaz Khan; Haris Wazir Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Optimized biosurfactant production from coconut shell extract by Bacillus wiedmannii isolate adopting an explainable artificial neural network and TOPSIS framework - Humaira Mukadam; Nageswar Sahu; Shikha Gaikwad; Biswanath Mahanty (Biocatalysis and Agricultural Biotechnology, 2026)

Analyzing Water Demand and Supply Under Socioeconomic and Climate Change Scenarios Using WEAP: a Case Study of Kabul River Basin, Pakistan - Humaira Abid; Javed Iqbal; Adnan Abbas Shah; Aiman Zafar (Water Conservation Science and Engineering, 2026)

Water quality and pollution sources in the coastal region of Balochistan, Pakistan: a call for sustainable coastal water management - Humaira Kanwal; Lubna Ghazal; Suraiya Jabeen; Muhammad Arsalan; Syed Wasi Haider (Journal of Coastal Conservation, 2026)

Geospatial Assessment of Freshwater Quality for Heavy Metals and its Potential Health Risks Using Geoinformatics and Water Index Models in Gilgit-Baltistan-Pakistan - Naila Jabeen; Lubna Ghazal; Humaira Kanwal; Tayyab Raza Fraz; Muhammad Farrakh Nawaz; Liaquat Karim; Faten Khalid Karim; Samih M. Mostafa; Altaf Hussain Lahori (International Journal of Environmental Research, 2026)
Access to safe drinking water is a growing global challenge, with billions of people exposed to water scarcity and contamination risks. Heavy metals in drinking water are of particular concern due to their toxic effects on human health and ecosystems. This study assessed the drinking water quality of Hunza Valley, Gilgit-Baltistan, Pakistan, where no comprehensive geospatial evaluation had previously been conducted. A total of 66 water samples from springs and glaciers were analyzed for physico-chemical parameters and heavy metals (Fe, Ni, Cd, Cr-VI, As, and Pb). Statistical analysis (correlation, principal component analysis and cluster analysis), water quality indices (Water Quality Index and Synthetic Pollution Index), human health risk assessment (Hazard Quotient and Hazard Index) and geostatistical interpolation (Ordinary Kriging) were employed. Results showed that As (77%), Pb (34%), Cd (25%), and Cr-VI (9%) exceeded WHO limits, while Fe and Ni remained within permissible levels. WQI classified 59% of samples as unfit for human consumption, while SPI designated 26% as unsafe. PCA extracted four significant factors explaining 67% of total variance, and hotspot mapping highlighted Aliabad, Dorkhun, and Ganish as most contaminated villages. The hazard quotient and hazard index for non-carcinogenic health risk showed very few samples with significant health risk. The geospatial maps of health risk showed higher geospatial variability for arsenic, lead and iron whereas low variations were observed for cadmium, chromium and nickel. The TCRI values revealed As, Cd, Cr, Pb and Ni pose significant carcinogenic health risk with geospatial variation highlighting the western side of the district. The findings emphasize the urgent need for feasibility studies for treatment facilities, regular monitoring, cancer specific health risk studies to protect public health in Hunza Valley. This research provides a framework for sustainable water management aligned with SDG-6.

Harnessing the Potential of Nodule Endophytic Bacteria to Improve Soybean Growth Under Saline Conditions - Humaira Islam; Mohsin Tariq; Kashif Sattar; Tahira Yasmeen; Muhammad Abdul Rehman Rashid (Current Microbiology, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Can baxdrostat redefine blood pressure control in resistant and uncontrolled hypertension? a systematic review, meta-analysis, and trial sequential analysis - Bilal Wazir Khan; Muhammad Yahya; Hamza Wazir Khan; Miguel Alejandro Rivas Perez; Tayyaba Ikram Qazi; Humaira Obaid; Muhammad Mustafa Khan; Muhammad Maaz Amjad; Muhammad Faaz Khan; Aneeq Mahmood Khan; Muhammad Junaid Khan; Sajjad Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comparative phytochemical profiling, antioxidant, and antibacterial activities of jute (Corchorus spp.), kenaf (Hibiscus cannabinus), and mesta (Hibiscus sabdariffa) using different extraction systems - Taslima Rahman; Humaira Akhter; Zakaria Ahmed; Md. Anowar Hosen; Anowara Begum (Vegetos, 2026)

In silico identification of novel PTP1B inhibitors by the investigation of molecular mechanism, QSAR, and DFT studies - Humaira Zulfiqar; Samira Akter; Jarin Tasnim; Muhammad Younis; Md. Mehedi Hasan; Sidra Manzoor; Sarnop Sarker; Muhammad Waqas; Khan Rajib Hossain (In Silico Pharmacology, 2026)
Protein tyrosine phosphatase 1B (PTP1B) is a well-known and promising drug target involved in the negative regulation of insulin and leptin signaling, and new anti-diabetic molecules for the treatment of type 2 diabetes are directly in its hands. A series of PTP1B inhibitors was discovered and characterized using in silico techniques, including virtual screening, molecular docking, ADMET profiling, toxicity prediction, VEGA-QSAR analysis, molecular dynamics (MD) simulation, and density functional theory (DFT) calculations. A starting library of 1000 anti-diabetic compounds was screened, and PubChem CID 44560696 was identified as the most successful hit. The most potent inhibitor was then identified as CID 44560744 through chemical analogy-based refinement, with a binding free energy of − 9.13 kcal/mol and the ability to form several stabilizing hydrogen bonds and hydrophobic interactions with the key catalytic residues. DFT-optimized geometry and docking revealed that the lead compound shows high stability and strong PTP1B inhibition, showing superior binding affinity compared to ursolic acid, which exhibited a lower binding energy of − 6.34 kcal mol −1 . The MD simulations showed that the PTP1B-ligand complex was structurally stable and compacted during the 200 ns simulation, with desirable profiles for RMSD, RMSF, Rg, SASA, and hydrogen bonds. The DFT and FMO analyses indicated that the compound exhibits extreme chemical reactivity and electron-transfer capability, owing to its low HOMO-LUMO gap, high softness, and moderate electrophilicity. The results of ADMET and toxicity evaluations (SwissADME, ProTox-II, and VEGA-QSAR) pointed to satisfactory solubility, non-carcinogenicity, no mutagenicity, and high pharmacological safety. Overall, the synergy of the computational methods has made CID 44560744 a lead scaffold for the development and optimization of selective PTP1B inhibitors for T2DM therapy.

Integrated spatial analysis and Gaussian dispersion modelling of airborne particulate matter from rice processing mill hubs in rural Bangladesh and associated public health risks - Rubaiatul Islam Zerin; Md. Kamrul Hossain; Humaira Rashid; Sababa Tasnim; Md. Julfikar Ali; Md. Mizanur Rahman; Mohd. Maniruzzaman; Rafiquel Islam (Environmental Science and Pollution Research, 2026)

Elucidating ACE2 Variants: A Genetic Insight into Essential Hypertension in the Bangladeshi Population - Sonia Tamanna; Abdullah Al Saba; Taslimul Jannat; Zimam Mahmud; Mohammad Shakil Mahmood; Humaira Binte Asad; Md. Zakir Hossain Howlader (Indian Journal of Clinical Biochemistry, 2026)

Systems-level genomic and functional characterization of lipopeptide biosurfactant pathways in Bacillus albus MITWPUB5 - Humaira Mukadam; Tanishka Bhujbal; Kausik Bhattacharyya; Shikha Gaikwad (World Journal of Microbiology and Biotechnology, 2026)

Biocontrol of powdery mildew in luffa by the silicon-solubilizing endophytic fungi from Trichoderma koningii and Aspergillus clavatus - Asim Ur-Rahman; Sundus Rauf; Khalil Ur Rahman; Mamoona Rauf; Humaira Gul; Alaa Baazeem; Mohamed M. Hassan; Muhammad Hamayun; Muhammad Arif (Physiological and Molecular Plant Pathology, 2026)

Multigene identification, phylogenetic resolution, and morpho-pathogenic characterization of Fusarium commune and Fusarium solani causing wilt in chilli from the Kashmir - Zohra Shabir; Shaheen K. Jan; Farooq A. Bhat; Mir Mehreen; Zakir Amin; Rakshanda Anayat; Fehim J. Wani; M.H. Chesti; Sajad Un Nabi; Sheezana Rasool; Suhail Ashraf; Tanveer Ahmad Wani; et al. (Physiological and Molecular Plant Pathology, 2026)

Integrated TiO2 Nanoparticles and Pseudomonas sp. GM5 Lower Tissue Chromium Concentrations and Strengthen Physiological Resilience in Wheat under Chromium and Drought Stress - Saba Javid Qazi; Humaira Yasmin; Urooj Farid; Zeeshan Ahmad; Asia Nosheen; Tariq Sultan; Naeem Khan; Abdulaziz Abdullah Alsahli (Biocatalysis and Agricultural Biotechnology, 2026)

Therapeutic evaluation of artocarpin-enriched extract from Artocarpus heterophyllus heartwood in multiple sclerosis rat model - Humaira Majeed; Rizwan Rashid Bazmi; Malik SaadUllah; Zunera Chauhdary (Inflammopharmacology, 2026)

Determination and degradation behaviour of thiram and carbendazim by using dispersive liquid to liquid micro extraction - Humaira Razaq Khan; Nusrat Bibi; Nurfaizah Abu Tahrim; Aziza Sarwar; Muhammad Nawaz; Bibi Sherino (Environmental Monitoring and Assessment, 2026)

Carbonated manufactured sand as a sustainable substitute for natural fine aggregates in mortar - Humaira Athar; Deepika Saini; Kishor Sitaram Kulkarni; Srinivasarao Naik Bhanavath; Anish Kushwah (Environmental Science and Pollution Research, 2026)

Spatial Distribution and AirQ + -Based Health Risk Analysis of Particulate Matter in Bangladesh’s Industrial Hubs - Md. Kamrul Hossain; Rubaiatul Islam Zerin; Humaira Rashid; Umma Suraiya Parvin Kakon; Mst. Sadia Siddika Trina; Laila Anjum Eva; Shahin Ali; Mohammad Omar Faruk Molla; Md. Saikoth Jahan; Md. Assraf Seddiky; Sazal Kumar; Mohd. Maniruzzaman; et al. (Water, Air, & Soil Pollution, 2026)
Rapid urbanisation and population growth in Bangladesh have intensified ambient particulate matter (PM 2.5 and PM 10 ) pollution, posing critical threats to public health. This study assessed PM concentration in three major industrial cities, Dhaka, Narayanganj, and Gazipur. PM concentrations were measured using an Air Particle Counter and an optimised air-quality sensor. PM measurements were conducted at 138 sampling points across Dhaka, Narayanganj, and Gazipur in October 2023, a climatologically stable late-autumn period, providing a reliable baseline for assessing ambient PM levels. Long-term chronic and acute diseases were quantified using the WHO AirQ + tool, including acute lower respiratory infection (ALRI) in children, chronic obstructive pulmonary disease (COPD), ischemic heart disease (IHD), stroke, and lung cancer (LC) in adults. The study revealed that the average PM 2.5 concentrations of 74.04, 56.70, and 63.99 µg/m 3 exceeded WHO standards in three cities and exceeded BD standards only in Dhaka, while PM 10 levels exceeded only WHO standards. A strong correlation was observed between PM 2.5 and PM 10 . Meteorological analysis indicated that wind speed and direction were key dispersion drivers, whereas temperature and humidity showed weak inverse exponential relationships with PM levels. Hazard Quotient (HQ) derivation revealed significant non-cancer health risks, with values exceeding unity. In contrast, PM 2.5 significantly affected ALRI mortality among children, with rates of 0.52, 0.44, and 0.49 per 100,000 in Dhaka, Narayanganj, and Gazipur, respectively. In adults, stroke was the leading PM 2.5 -related cause of death, with rates of 9.87, 9.13, and 9.63 per 100,000 in these cities. IHD deaths were also high, while LC and COPD mortality ranged from low to moderate. The study underscores the substantial public health implications of persistent PM pollution across Bangladesh’s industrial cities and reinforces the urgency of implementing coherent regulatory interventions. To strengthen the precision of exposure assessments and support more robust evidence-based policymaking, future investigations should incorporate multi-seasonal sampling, extended temporal monitoring, and broader spatial representation across diverse industrial zones.

Tagetes minuta L. Extract Ameliorates Epilepsy: Modulating Neuroinflammatory Pathways via Altering Brain-Derived Neurotropic Factor and Interleukin-6 Levels - Maryum Mumshad Raja; Humaira Naureen; Fawad Ali Shah; Sadia Adil; Arooj Mohsin Alvi; Rabia Khan; Sundas Safdar; Farah Azhar; Shahana Khattak (Journal of Pharmaceutical Innovation, 2026)

Phycoerythrin from algae: functional properties, bioactivities, production challenges, and industrial prospects - Ashiq Ali; Humaira Muzaffar; Shatha Ali Hassoun; Muhammad Afzaal; Catherine Tamale Ndagire (Archives of Microbiology, 2026)

Toxicity assessment of Mitragyna speciosa leaf extracts using zebrafish ( Danio rerio ) embryos and analysis of their Q-TOF LCMS chemical profiles - Taslima Begum; Qamar Uddin Ahmed; Mohd Hafiz Arzmi; ABM Helal Uddin; Syed Adnan Ali Shah; Mohd Salleh Rofiee; Humaira Parveen; Sayeed Mukhtar; Uzma Faridi; Sharifah Nurul Akilah Syed Mohamad; Alfi Khatib (Natural Product Research, 2026)

Biosynthesis of rhamnolipids from waste cooking oil by Pseudomonas aeruginosa RW9 with insights into stability and toxicity performance - Zee Kar Mun; Nur Humaira Adlin Hassan Adli; Siti Syazwani Mahamad; Mohd Nazren Radzuan; Mohd Noriznan Mokhtar; Mohd Rafein Zakaria (Systems Microbiology and Biomanufacturing, 2026)

Antimicrobial and antioxidant activities of Tetracera macrophylla Hook.f. & Thomson leaf extracts: insights from Q-ToF-LCMS, pharmacokinetics and molecular docking approach - Qamar Uddin Ahmed; Muhammad Akmal Hakim Ab Rahim; Mohd Hafiz Arzmi; ABM Helal Uddin; Syed Adnan Ali Shah; Mohd Salleh Rofiee; Humaira Parveen; Sayeed Mukhtar; Uzma Faridi; Nurul Hidayah Mohd Rosedi; Murni Nazira Sarian; Taslima Begum (Natural Product Research, 2026)

Barleria Lupulina Lindl. as a reservoir of bioactive compounds: A multi-analytical botanical substances investigation - Anam Nizam; Syed Naved Quadri; Afifa Ansari; Humaira Farooqi (South African Journal of Botany, 2026)

Biobased materials in the circular economy: A strategic review on the advanced functionalization and applications of biopolymers - Syed Kashif Ali; Abdullah Ali Alamri; Faris Alfifi; Hassien M. Alnashiri; Humaira Parveen; Sayeed Mukhtar; Shaily; Liyaqat Ali Kamran; Mohd Waseem; Adnan Shahzaib (Journal of Environmental Chemical Engineering, 2026)

Impacts of political instability and green technology on carbon emissions and climate change in Chad: evidence from NARDL - Yasir Khan; Humaira Yousafzai; Constant Dingamadji Bounade; Li Xiangdong; Majid Khan; Zi Yang Shen (Theoretical and Applied Climatology, 2026)

Application of Melatonin and Bacillus halotolerans Mitigated the Cadmium and Lead Induced Toxicity in Brassica carinata by Improving the Growth and Defense System of the Plant - Namra Batool; Asia Nosheen; Humaira Yasmin; Rabia Naz; Paul A. Correa; Syed Muhammad Usman Shah Kazmi (Journal of Plant Growth Regulation, 2026)

Genome-Wide Association Study Reveals Marker-Trait Associations and Genes Linked To Cold Tolerance during Developmental Stages in Rice - Humaira Jan; Gazala H. Khan; Mahandiya Iqbal; Asif B. Shikari; N. R. Sofi; Raheel Shafeeq Khan; Parvaiz. A. Sofi; Zahida Rasheed; Mohammad Saleem Dar; Fehim Jeelani Wani; Khairiah Mubarak Alwutayd; Shabir Ahmad Ganai; et al. (Journal of Plant Growth Regulation, 2026)

Integrated GC–MS phytochemical analysis and in vivo assessment of antiarthritic activity of Curcuma zedoaria extracts - Yusra Wasti; Syeda Aroosa Mohsin; Muhammad Tahir Aqeel; Sania Atta; Nadeem ul Hassan Khan; Syeda Ayesha Farhana; Humaira Fatima; Iffat Naz (Inflammopharmacology, 2026)

Retraction Note: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2026)

Synergistic Interaction Between Alkanna tinctoria (L.) Tausch and Cefixime Enhances Antibacterial Activity Against Resistant Bacterial Strains - Amber Sadiq; Aroosa Zafar; Iffat Naz; Nadeem Irshad; Ihsan ul Haq; Sohail Ahmed; Nosheen Akhtar; Humaira Fatima (Current Microbiology, 2026)

Molecular prevalence, genetic diversity and effect of Toxoplasma gondii infection on the hematological parameters of various bird species - Tauqir Un Nisa; Fatima Mushtaq; Humaira Zulfiqar Ali Gondal; Naila Amjad; Muhammad Usman; Muhammad Ali; Muhammad Latif; Hira Muqaddas; Furhan Iqbal (Biologia, 2026)

Surface-modified ZnSe nanoparticles for removal of cadmium (Cd2+) ions from water - Khurshed A. Shah; Faheem A Shiekh; Humaira S. Wani; S.M.A. Andrabi; Prabhakar Misra (Next Research, 2026)

Anti-inflammatory and anti-allergic potential of liquiritin extracted from Glycyrrhiza glabra L. in asthma management - Zara Guftar†; Humaira Majeed Khan; Areej A. Alosaimi†; Modhi O. Alotaibi; Aisha Umar; Lala Gurbanova; Marek Gancarz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Co-application Impacts of Silicon and Potassium Fertilizers on Wheat (Triticum Aestivum L.) Growth and Nutritional Attributes in Cadmium-contaminated Soil Under Two Irrigation Regimes - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Rizwan; Qamar uz Zaman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Shabir Ahmad; Lala Gurbanova; Rashid Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Regulation of biochemical attributes, photosynthetic pigments, and antioxidant activity in Zea mays L. for complete amelioration of heavy metal toxicity using synergistic application of arsenic-tolerant PGPR and nanoparticles - Mohsin Zafar; Humaira Yasmin; Tayyab Shafiq; Rabia Naz; Asia Nosheen; Muhammad Nadeem Hassan (Environmental Science and Pollution Research, 2026)

Aspergillus flavus and Colpomina sinousa mixture act as biocatalyst to improve growth, fruit yield and salinity resistance of Brassica napus for sustainable agriculture - Hira Wahid; Humaira Gul; Mamoona Rauf; Asma Tabassum; Aliya Rehman; Muhammad Arif; Muhammad Hamayun; Hatem E. Semary; Zainul Abideen (Biocatalysis and Agricultural Biotechnology, 2026)

Anti-arthritic and anti-inflammatory effects of BMZD-2CPE in a CFA and carrageenan-induced animal model - Samiullah Wazir; Farah Abid; Aisha Mobashar; Arham Shabbir; Muhammad Awais; Humaira Nadeem; Hafiz Aamir Ali Kharl; Esmael M. Alyami; Amir Bouallegue; Norah Hamdi; Mohammed Bourhia; Abdullah R. Alanzi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Caffeoylquinic acid derivatives isolated from Tussilago farfara L. as potential anti-leishmanial agents; in vitro and in silico studies - Izaz Ahmad; Salar Hafez-Ghoran; Muhammad Yousuf; Humaira Zafar; Atia-tul- Wahab; Sammer Yousuf; Mushtaq Ahmad; Inam Gul; Bates Kudaibergenova; M. Iqbal Choudhary (Natural Product Research, 2026)

Meloxicam Eluting 3D Printed 316L Stainless Steel Implants for Targeted Delivery in Bone Fixation Surgeries - Manjusha Annaji; Ishwor Poudel; Nur Mita; Chu Zhang; Humaira Yeasmin; Seungjong Lee; Peter Panizzi; Robert D. Arnold; Amal Kaddoumi; Nima Shamsaei; Byron Farnum; Oladiran Fasina; et al. (AAPS PharmSciTech, 2026)
Implant failures in orthopedic surgeries can occur due to inflammation, poor osteointegration, and biofilm formation. The local delivery of anti-inflammatory drugs is one of the potential solutions to address orthopedic implant failures caused by extensive inflammation, poor osteointegration, and biofilm formation. This study utilized a simple spray coating technique to deposit multilayer coatings of the anti-inflammatory drug meloxicam and PLGA on 3D printed 316L stainless steel implants. The implants were evaluated for their drug content, drug-polymer miscibility, static contact angle, corrosion resistance, in vitro release, cell adhesion, cell proliferation, and bacterial adhesion studies. The coatings aimed to improve osteointegration and reduce biofilm formation. The drug release studies demonstrated an initial burst release accompanied by sustained release for more than 30 days. The meloxicam-PLGA coated implants showed higher resistance to pitting corrosion, improved adhesion, and proliferation of human U2OS cells in comparison to uncoated implants. In addition, results from cell cytotoxicity studies confirmed that all the coatings are biocompatible and safe for in vivo application. The meloxicam-PLGA coated implants were also found to have significantly lower bacterial adhesion and biofilm formation compared to uncoated implants for both S. aureus ( p S. pseudintermedius ( p Graphical Abstract

Identification and fine-mapping of novel major locus for yellow mosaic disease resistance in Glycine soja - Ashita Bisht; Asmita Sirari; Virender Kumar; Abhishek Sharma; Gaurav Khosla; Shalaka Ahale; Humaira Sonah; Balwinder Singh Gill (Plant Cell Reports, 2026)

Flavonolignans from Lannea acida A. Rich. as potential antileishmanial agents - Muhammad Aamer; Muhammad Kamran; Muhammad Yousuf; Kayode Muritala Salawu; Humaira Zafar; Atia-tul Wahab; M. Iqbal Choudhary; Farooq-Ahmad Khan; Yan Wang (Natural Product Research, 2025)

Bioprospecting Artemisia roxburghiana Wall. ex Besser extracts for their potential antimicrobial, antiprotozoal, antidiabetic and anticancer potential - Syeda Masooma Ali; Sara- Tun-Nisa; Muhammad Majid; Humaira Fatima; Ihsan- ul-Haq (Natural Product Research, 2025)

Pathogenic CDKN2A germline variants are rare in a cohort of unselected pancreatic cancer patients from Pakistan - Shumaila Arif; Noor Muhammad; Humaira Naeemi; Muhammad Usman Rashid (Familial Cancer, 2025)

Synergistic effects of selected ethnomedicinal plants with Metronidazole against resistant H. Pylori, and their urease inhibition mechanism - Sania Atta; Marya Nawaz Malik; Muhammad Tahir Aqeel; Iffat Naz; Nadeem Irshad; Sadaf Naz; Nadeem ul Hassan Khan; Faisal Rasheed; Humaira Fatima (South African Journal of Botany, 2025)

How can renewable energy and strategic trade practices mitigate climate change severity in lower-middle-income economies? - Yasir Khan; Humaira Yousafzai; Constant Dingamadji Bounde; Xiangdong Li; Yi-Cheng Yeh (Theoretical and Applied Climatology, 2025)

Association of PD-1 immune checkpoint polymorphisms with oral cancer risk: results from a Pakistani case-control study - Iqra Mubeen; Arifa Shabbir; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Muhammad Usman Rashid; Naila Malkani (Molecular Biology Reports, 2025)

The impact of germination time on nutritional and antioxidant properties of selected cereals - Fahid Nazir; Hamza Zahid; Muhammad Riaz; Yahya Mushtaq; Natasha Amjad; Humaira Iqbal; Muhammad Rizwan Majeed; Shazia Kousar; Muhammad Ahmad Mudassir (Cereal Research Communications, 2025)

Comparative study of extraction methods and process parameters of polyphenolic content obtained from Celosia argentea L. Flower for herbal sunscreen - Humaira Arshad; Adnan Afzal; Arifa Mehreen; Faiza Shakoor; Valisher Sapayev Odilbek Uglu; Saima Qadeer; Samiyah Tasleem; Rana Muhammad Kamran Shabbir; Mukhayya Djumaniyazova (Natural Product Research, 2025)

Operational performance of ventilation mechanisms for layer houses: Modeling with experimental validation - Kasra Ghasemi; Sifat Tasnim Oishique; Syeda Humaira Tasnim; Marta Sokolowski; Tahereh Gorji-Bandpy; Shohel Mahmud (Computers and Electronics in Agriculture, 2025)

Recent advances in conducting polymers for hybrid solar-driven evaporation systems: Fundamentals, innovations, and applications - Bushra Shakoor; Muhammad Sultan Irshad; Uzma Ghazanfar; Humaira Razzaq; Naila Arshad; Ghazala Maqsood; Iftikhar Ahmed; Muhammad Atif Ali; Muhammad Sohail Asghar; Irshad Hussain; Tao Mei; Tran Vinh Dieu; et al. (Chemical Engineering Journal, 2025)

Biofunctional and ecotoxicological assessment of Rosa indica derived nitrogen-doped Carbon Dots: A new frontier for sustainable nanomaterials - Hubza Ruatt Khan; Humaira Yasmeen; Muhammad Asad Tahir; Asna Fatima Kiani; Iqra Munir; Unzish Qamar; Sara Janiad; Saher Mahmood (Biocatalysis and Agricultural Biotechnology, 2025)

Performance of sustainable ternary blended concrete using rice husk ash and metakaolin as partial cement substitutes - Kamrul Hasan; Humaira Khatun; Roni Mazumder; Ramadhansyah Putra Jaya; Fadzil Mat Yahaya (Innovative Infrastructure Solutions, 2025)

Chemical insights into a bioactive polyphenolic extract from Camellia japonica L. flower - Humaira Khan; Lara Comune; Simona Piccolella; Severina Pacifico (Phytochemistry Letters, 2025)

Sustainable wastewater treatment via nitrogen/sulfur co-doped graphene composite: Mechanistic insights & process optimization - Humaira Seema; Muhammad Arshad; Arslan Maqbool; Sumbal Zeb; Ali Hamid; Muhammad Umar; Sajjad Hussain; Hammad Khan (Journal of Water Process Engineering, 2025)

DFT investigation of pristine and li-functionalized TiS2 monolayers for toxic gas sensing applications - Zunaira Saleem; Saleh S. Alarfaji; Humaira Shaheen; Abdul Majid; Muhammad Isa Khan (Journal of Environmental Chemical Engineering, 2025)

Reassessing technological progress in the era of climate change: the role of green energy, R&D, and high-tech in emission mitigation - Yasir Khan; Humaira Yousafzai; Constant Dingamadji Bounade; Li Xiangdong (Theoretical and Applied Climatology, 2025)

Correction: Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Selenium mitigates boron toxicity in Nicotiana tabacum via altering root anatomy, accumulation of boron, biochemical and physiological aspects - Ghulam Murtaza; Zeeshan Ahmed; Gang Deng; Sohail Akhtar; Muhammad Rizwan; Muhammad Usman; Mona S. Alwahibi; Humaira Rizwana; Tolga İzgü; Özhan Şimşek; Rashid Iqbal; Faisal Zulfiqar (Plant Biosystems, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

GC-MS profiling and biological investigations of Cissampelos pareira L. & Lantana camara L. - Muhammad Wasim; Hafiz Abdul Rafey; Sadia Sarwar; Humaira Nadeem; Samir Anis Ross; Farhat Shaheen (Natural Product Research, 2025)

Dietary protein deficiency exacerbates perfluorohexane sulfonate (PFHxS)-induced reproductive abnormalities and metabolic disruptions in female rats - Suramya; Mehjbeen Javed; Anuradha Mangla; Suraj Kumar; Shaesta Shahid; Humaira Naaz Bhutto; Shahzad Ahmad; Basir Ahmad; Sheikh Raisuddin (Reproductive Toxicology, 2025)

Effect of MXenes, nZVI and Acacia-wood Biochar Treatments on Bioavailability Pb and Fractions in Calcareous-polluted Soils - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Usman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Rashid Iqbal (Water, Air, & Soil Pollution, 2025)

Synthesis, biological evaluation, and in silico studies of chalcone-based ketamine derivatives with preferential COX-2 inhibitory activity - Syed Muzzammil Masaud; Humaira Nadeem; Abida Shamim; Muhammad Kazim Zargaham; Usman Shareef; Sana Ayaz; Babar Murtaza (Medicinal Chemistry Research, 2025)

Anti-inflammatory and gastroprotective effects of Fagonia bruguieri var. laxa (Zygophyllaceae) via attenuating biochemical alterations and cellular damage in experimental animals - Faraza Javaid; Humaira Gul; Farhan Mukhtar; Salman Farsi; Sana Ghafoor; Hafiza Maida Arshad (Inflammopharmacology, 2025)

Pollen micromorphology and its taxonomic significance in the selected melliferous taxa of Upper Dir, Khyber Pakhtunkhwa: insights for honeybee-plant interactions - Tariq Ullah; Muhammad Zafar; Mushtaq Ahmad; Hussain Shah; Shabir Ahmad; Hossam M. Aljawdah; Humaira Rizwana; Rashid Iqbal; Muhammad Aizaz; Muhammad Abdullah (Genetic Resources and Crop Evolution, 2025)

Combination of Sargassum wightii extract and pyridoxin mixture improves growth and salinity tolerance in Okra for sustainable agriculture - Zawar Khan; Humaira Gul; Aliya Rehman; Asma Tabassum; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Mohamed A. El-Sheikh; Zainul Abideen (Algal Research, 2025)

Platelet-Rich Plasma (PRP) Mitigates Kidney Dysfunction in Alloxan-Induced Diabetic Mice via Modulation of Renal Iron Regulatory Genes - Humaira Allay Ali; Muddasir Hassan Abbasi; Tasleem Akhtar; Amin Arif; Mehreen Anjum; Sana Fatima; Rabia Mehmood; Adil Farooq; Nadeem Sheikh; Muhammad Babar Khawar (Biochemical Genetics, 2025)

Spectrum of BRCA1/2 pathogenic variants in Southern and Western Asia-a systematic review - Samra Khan; Ikram A. Burney; Mahrukh Nasir; Humaira Saleem; Muhammad Irfan; Muhammad Shakeel; Ishtiaq Ahmad Khan (Mutation Research - Reviews in Mutation Research, 2025)

Machine learning-driven hybrid cooling system for enhanced energy efficiency in multi-unit residential buildings - Mehran Bozorgi; Syeda Humaira Tasnim; Shohel Mahmud (Energy and Buildings, 2025)

Fe-Modified Biochar Improves Tobacco Productivity by Promoting Root Growth, Plant Biochemical Traits and Nicotine Level: A Three Years Field Study - Ghulam Murtaza; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Mona S Alwahibi; Humaira Rizwana; Javed Iqbal; Muhammad Qasim; Rashid Iqbal; Gang Deng (Journal of Soil Science and Plant Nutrition, 2025)

Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Role of polyphenolics in the management of rheumatoid arthritis through intracellular signaling pathways: a mechanistic review - Uzma Saleem; Maryam Farrukh; Malik Saadullah; Rida Siddique; Humaira Gul; Aqsa Ahmad; Bushra Shaukat; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Multi-Step Synthesis, Characterization and Physicochemical Investigation of Benzylated Indole Thiosemicarbazone as Selective Switch on Sensing Properties for Copper Ion - Md. Zafer Alam; Suhail Ahmad; Md. Mohasin; Umme Salma; Alimuddin; Humaira Parveen; Sayeed Mukhtar; Salman A. Khan (Journal of Fluorescence, 2025)

Advancing circular economy in the equipment manufacturing sector: The role of environmental management systems, innovation and policy support - Humaira Yasmeen; Cheng Longsheng (Journal of Environmental Management, 2025)

In-Situ Self-Transformation Growth of Binary g-C3N4/CdS Heterojunctions for Efficient Hydrogen Evolution and Wastewater Treatment - Muhammad Irfan; Muhammad Shoaib; Humaira Hussain; Muhammad Yasin Naz; Shazia Shukrullah; Saifur Rahman; Salim Nasar Faraj Mursal; Abdulnour Ali Jazem Ghanim (Water, Air, & Soil Pollution, 2025)

Regulating the NMDA/NR2B signaling pathway mediates anticonvulsant, antineuroinflammation, and anti-oxidative stress effects of 1,3,benzothiazole derivative 1M in pentylenetetrazole-induced kindling in mice - Neelum Gul Qazi; Ayesha Shafique Malik; Arooj Mohsin Alvi; Fawad Ali; Ismail Badshah; Humaira Nadeem; Sohaib Zafar Malik (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Safety assessment of novel oxadiazole derivatives in acute and sub-acute toxicity studies - Syeda Rida Zainab; Jehan Zeb Khan; Humaira Nadeem; Muhammad Khalid Tipu; Nadeem Irshad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Protective Effects of Multiple-Chemical Engineered Biochar On Hormonal Signalling, Antioxidant Pathways and Secondary Metabolites in Lavender Exposed to Chromium and Fluoride Toxicity - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Qamar uz Zaman; Gang Deng; Suiyun Chen; Mona S. Alwahibi; Humaira Rizwana; Javed Iqbal; Shabir Ahmad; Rashid Iqbal (Journal of Crop Health, 2025)

Nanoparticle-Mediated Phytohormone Interplay: Advancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Fozia Farhat; Saher Nawaz; Muhammad Ahmad (Journal of Crop Health, 2025)

Effect of Junk Food on Hormonal and Metabolic Manifestations in Polycystic Ovarian Syndrome Phenotypes: A Case–Control Study of Kashmiri Population - Khair Ul Nisa; Najeebul Tarfeen; Shahnaz Ahmad Mir; Zulaykha Khurshid; Mir Bilal Ahmad; Saba Wani; Humaira Bhat; Bashir Ahmad Ganai (Indian Journal of Clinical Biochemistry, 2025)

A review on Mitragyna speciosa (Rubiaceae) as a prominent medicinal plant based on ethnobotany, phytochemistry and pharmacological activities - Taslima Begum; Mohd Hafiz Arzmi; Alfi Khatib; A.B.M. Helal Uddin; Maryam Aisyah Abdullah; Kamal Rullah; Siti Zaiton Mat So’ad; Nur Fatihah Zulaikha Haspi; Murni Nazira Sarian; Humaira Parveen; Sayeed Mukhtar; Qamar Uddin Ahmed (Natural Product Research, 2025)

Bilateral carotid-cavernous fistulas following trauma: A rare case of diagnostic and management challenges - Allahdad Khan; Nehan Zahoor; Humaira Siddique; Javed Iqbal (Acta Neurologica Belgica, 2025)

Fronds micromorphology of anatomical parameters among selected ferns species in Uzbekistan - Dilshodjon Muminov; Khislat Khaydarov; Muhammad Zafar; Humaira Rizwana; Mohamed Soliman Elshikh; Trobjon Makhkamov; Salman Majeed; Islamov Boston Sultanovich; Ilkhom Mukumov; Zebiniso Umurzakova; Murtoza Hasanov; Zebo Rasulova; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Significance of Selenium in Improving the Yield and Quality of Quinoa Under Drought - Muhammad Usman Aslam; Muhammad Aown Sammar Raza; Rashid Iqbal; Salman Ahmad; Imran Haider; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Saltanat Aghayeva; Nazim S. Gruda (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2025)

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Bisphenol A-induced polycystic ovary syndrome (PCOS) with hormonal and metabolic implications in rats - Mehjbeen Javed; Suramya; Anuradha Mangla; Garima Jindal; Humaira Naaz Bhutto; Shaesta Shahid; Suraj Kumar; Sheikh Raisuddin (Reproductive Toxicology, 2025)

Combined pharmacological and computational approaches unraveling the protective effects of Cassia angustifolia extract against NANO2 - induced neurodegeneration and hepatotoxicity - Shabina Ishtiaq Ahmed; Humaira Ismatullah; Qaisar Mansoor; Muhammad Yaseen; Aisha Naveed; Muhammad Qasim Hayat; Saadia Zahid; Junaid Arshad; Mubarra Tahir; Mashooq Ahmad Bhat (Food Bioscience, 2025)

Allelic variation in major genes and quantitative trait loci associated with grain number in historical spring wheat cultivars - Muhammad Aamir Khan; Yuanyuan Tian; Humaira Qayyum; Benish Iltaf; Youshaa Danyal; Muhammad Amjad Farooq; Muhammad Kashif Ilyas; Zahid Mahmood; Shoaib-ur-Rehman; Jindong Liu; Awais Rasheed (Genetic Resources and Crop Evolution, 2025)

Antibacterial activity and synergistic interaction between Artemisia roxburghiana Wall. ex Besser extracts and synthetic antibiotics against resistant clinical isolates - Syeda Masooma Ali; Sara-Tun-Nisa; Humaira Fatima; Ihsan-ul-Haq (South African Journal of Botany, 2024)

Multi-target anticancer activity of compounds isolated from galls of Pistacia chinensis subsp. integerrima: A mechanistic investigation - Abdur Rauf; Majid Khan; Arsalan Nizamani; Humaira Hussain; Zuneera Akram; Yahya S. Al-Awthan; Hassan A. Hemeg; Omar S. Bahattab; Giovanni Ribaudo (Phytochemistry Letters, 2024)

Viola stocksii: A rich source of antioxidant and anti-inflammatory flavonoid glycosides with converged therapeutic potential against SARS-CoV-2 MPro, spike trimer, and surface glycoproteins - Roshan Zamir; Shanza Munir; Humaira Yasmeen Gondal; Muhammad Nisar; Sami A. Al-Hussain; Ahmed Abbaskhan; Zain M. Cheema; Magdi E.A. Zaki; M. Iqbal Choudhary (Food Bioscience, 2024)

In vitro regeneration strategy to revitalize Nyctanthes arbor-tristis L. using shoot stem explants: a sustainable way for medicinal plant conservation - Anushi A. Jahan; Iram Siddique; Humaira Rizwana (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Association between the variations in metabolic pathways and oral cancer risk: results from a Pakistani case-control study - Arifa Shabbir; Muhammad Usman Rashid; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Naila Malkani (Molecular Biology Reports, 2024)

Plant Biostimulants: Mechanisms and Applications for Enhancing Plant Resilience to Abiotic Stresses - Faizan Khalid; Yumna Rasheed; Kanza Asif; Humaira Ashraf; Muhammad Faisal Maqsood; Muhammad Shahbaz; Usman Zulfiqar; Rehana Sardar; Fasih Ullah Haider (Journal of Soil Science and Plant Nutrition, 2024)

Allelic variation in Puroindoline genes in synthetic hexaploid wheats and development of allele-specific PCR markers for new soft-texture alleles - Muhammad Aamir Khan; Yuanyuan Tian; Humaira Qayyum; Awais Rasheed; Zhonghu He (Cereal Research Communications, 2024)

Optimizing nitrogen application for improving yield and fruit quality in different peach cultivars - Muhammad Amin; Fayaz Ali; Sayed Sana Ullah Shah; Siraj; Humaira; Waqar Khan; Muhammad Shakur (Vegetos, 2024)

Adapting and validating the food neophobia scale for Pakistani mothers: Exploring the relationship between maternal and child food neophobia - Almab Zainab; Muhammad Jamal Khan; Syed Ubaid Ullah Shah; Humaira Wasila; Xiaoxi Shan; Tingwei Wang; Wenting Xu; Qian Lin (Food Quality and Preference, 2024)

Exploring the economic viability of electrochemical assessment for water contaminants with NiFe-PBA/ZIF-67 core shell modified GCE - Sharmila Tharuman; Tse-Wei Chen; Nandini Nataraj; Shen Ming Chen; Bih-Show Lou; Islem Abid; Humaira Rizwana; Mohamed Soliman Elshikh; Jaysan Yu (Environmental Research, 2024)

Enhancing sustainable mineral extraction through corporate social responsibility and green innovation - Humaira Yasmeen; Cheng Longsheng (Journal of Cleaner Production, 2024)

Optimization of protease production using Bacillus velezensis through response surface methodology and investigating its applications as stain remover - Humaira; Farah Deba; Hafiz Abdullah Shakir; Muhammad Khan; Marcelo Franco; Muhammad Irfan (Systems Microbiology and Biomanufacturing, 2024)

Allantoin regulated oxidative defense, secondary metabolism and ions homeostasis in maize (Zea mays L.) under heat stress - Humaira Yasmeen; Rizwan Rasheed; Muhammad Arslan Ashraf; Sadia Zafar; Shafaqat Ali (Physiology and Molecular Biology of Plants, 2024)

Correlation of Diabetes Related Factors with Vitamin D and Immunological Parameters in T2DM Kashmiri Population - Najeebul Tarfeen; Khair Ul Nisa; Shariq Rashid Masoodi; Humaira Bhat; Saba Wani; Bashir Ahmad Ganai (Indian Journal of Clinical Biochemistry, 2024)

Flavonoids from Pistacia chinensis subsp. integerrima with leishmanicidal activity: computational and experimental evidence - Abdur Rauf; Umer Rashid; Abdullah Muhammad Shbeer; Mohammed Al-Ghorbani; Naveed Muhammad; Anees Ahmed Khalil; Humaira Naz; Rohit Sharma; Giovanni Ribaudo (Natural Product Research, 2024)

Corrigendum to “Exogenous application of sodium hydrosulfide and salicylic acid mitigate salinity stress in maize by regulating ionic balance, biochemical attributes, photosynthetic pigments and some key antioxidants”, South African Journal of Botany 158 (2023) 393-404 - Sidra Shoukat; Ayesha Tassawar; Rumana Keyani; Mohsin Zafar; Rabia Naz; Asia Nosheen; Zafar Abbas Shah; Prashant Kaushik; Mohammed Nasser Alyemeni; Humaira Yasmin; Parvaiz Ahmad (South African Journal of Botany, 2024)

Exploring the vital role of phytohormones and plant growth regulators in orchestrating plant immunity - Ayesha Shafqat; Sonia Abbas; Madieha Ambreen; Ayesha Siddiqa Bhatti; Humaira kausar; Tabassum Gull (Physiological and Molecular Plant Pathology, 2024)

Effects of Withania somnifera (L.) Dunal in acute pulmonary pathophysiology in a rat model of smoke-induced lung injury and role of IRS-1 and SOX-2 - Sana Saleem; Imran Mukhtar; Hanan Y. Aati; Humaira Muzaffar; Haseeb Anwar; Musaddique Hussain; Maqsood Ahmad; Muhammad Umair; Kashif-ur-Rehman Khan (South African Journal of Botany, 2024)

Deciphering spatial-temporal dynamics of flood exposure in the United States, - Joynal Abedin; Lei Zou; Mingzheng Yang; Robert Rohli; Debayan Mandal; Yi Qiang; Humaira Akter; Bing Zhou; Binbin Lin; Heng Cai (Sustainable Cities and Society, 2024)

Enhancing Nutritional Self-Awareness and Course Engagement Through Personalized Dietary Assessment in Undergraduate Education - Jamshed Arslan; Humaira Jamshed (Journal of Nutrition Education and Behavior, 2024)

Enhancing Nutrition Literacy and Eating Behaviors Among Drug-Using Street Youth: A Foodways Perspective - Muhammad Ali; Humaira Jamshed (Journal of Nutrition Education and Behavior, 2024)

Retraction Note: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Transcriptomics of developing grains reveals putative candidate genes for grain zinc and iron in bread wheat cultivar Zincol-2016 - Samar Naseer; Mengjing Sun; Bushra Bibi; Humaira Qayyum; Muhammad Ramzan Khan; Chenyang Hao; Xueyong Zhang; Yuanfeng Hao; Awais Rasheed; Zhonghu He (Journal of Cereal Science, 2024)

Guar gum, Ulva lactuca L. biomass, and xanthan gum-based copolymer novel biosorbent for adsorptive removal of acid orange 10 - Samia Kanwal; Fozia Batool; Gulnaz Sharif; Hafiza Komal Naeem; Sobia Noreen; Humaira Yasmeen Gondal; Umar Bin Kamal; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Genetic diversity and population structure of Rubroshorea curtisii, a hill dipterocarp species: implications for conservation - Chin Hong Ng; Kevin Kit Siong Ng; Soon Leong Lee; Nur Nabilah Alias; Hazwani Humaira’ Zakaria; Lee Hong Tnah; Chai Ting Lee; Nurul-Farhanah Zakaria; Khairunnisa M. Mamat (Tree Genetics & Genomes, 2024)

Enhancing Plant Stress Resilience with Osmolytes and Nanoparticles - Yumna Rasheed; Faizan Khalid; Humaira Ashraf; Kanza Asif; Muhammad Faisal Maqsood; Nargis Naz; Muhammad Shahbaz; Usman Zulfiqar; Qasim Ali; Shamsa Rana (Journal of Soil Science and Plant Nutrition, 2024)

Extracellular Vesicles: A New Approach to Study the Brain’s Neural System and Its Diseases - Shahid Afridi; Pradakshina Sharma; Furqan Choudhary; Amber Rizwan; Anam Nizam; Adil Parvez; Humaira Farooqi (Cell Biochemistry and Biophysics, 2024)

Changing water sources and extraction methods in Bangladesh: Challenges, consequences, and sustainable solutions - Md. Jakariya; Mohammad Moshiur Rahman; Lamia Mahzabin; Adrita Chowdhury; Humaira Adiba; Md. Sajadul Alam; Mohammed Fahim Murshed; Christian Sonne; Damià Barceló; Junxu Chen; Md. Aminul Islam; Prosun Bhattacharya (Groundwater for Sustainable Development, 2024)

Developing a safe water atlas for sustainable drinking water supply in Sonargaon Upazila, Bangladesh - Md. Jakariya; Mohammad Moshiur Rahman; Lamia Mahzabin; Adrita Chowdhury; Humaira Adiba; M. Murshed Alam; Anika Islam; Tazin Mahmud Ashik; Turasa Nahla; Ibrahim Abdullah Mannan; Rifah Nanzibah; Khandaker Maisha Jahan; et al. (Groundwater for Sustainable Development, 2024)

Microbial goldmine: Investigating probiotic floral diversity in human breast milk - Ayesha Saeed; Azra Yasmin; Mehreen Baig; Maryam Pervaiz; Muhammad Arslan Ahmed; Muhammad Tabish; Humaira Hashmat (Bioactive Carbohydrates and Dietary Fibre, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

Multi-sensor Approach for the Estimation of Above-Ground Biomass of Mangroves - Humaira Sanam; Anjana Anie Thomas; Arun Prasad Kumar; Gnanappazham Lakshmanan (Journal of the Indian Society of Remote Sensing, 2024)

Ultrasound-Assisted Synthesis of Chalcone: A Highly Sensitive and Selective Fluorescent Chemosensor for the Detection of Fe3+ in Aqueous Media - Salman A. Khan; Md. Zafer Alam; Md. Mohasin; Suhail Ahmad; Umme Salma; Humaira Parveen; Sayeed Mukhtar; Menier Al-Anazi; Fatimah A. Alotaibi; Mahmoud A. Abdelaziz (Journal of Fluorescence, 2024)

Wound healing, antioxidant and antibacterial activities of polyphenols of Psidium guajava L. leaves - Kainat Bilal; Fatima Mehboob; Nosheen Akhtar; Irfan Ali Mirza; Muhammad K. Okla; M. Junaid Dar; Ibrahim A. Saleh; Naser Zomot; Humaira Fatima (South African Journal of Botany, 2024)

Occurrence of ochratoxin A in breast milk and urine samples of nursing mothers in Bangladesh - Aporajita Das Trisha; Jaasia Momtahena Hafsa; Akibul Hasan; Ahsan Habib; Humaira Rashid Tuba; Gisela H. Degen; Nurshad Ali (Mycotoxin Research, 2024)
The mycotoxin ochratoxin A (OTA) is a potent nephrotoxin with carcinogenic properties and, thus, of concern as a food contaminant. Since food contaminant data are scarce in Bangladesh, we applied human biomonitoring to gain more insights into OTA exposure in the country’s population. OTA concentrations in human milk and urine samples of nursing mothers were determined with the aim to assess also exposure to this mycotoxin in breastfed infants. Breastfeeding mothers (n = 74) from three districts of Bangladesh (Sylhet, Cumilla, and Mymensingh region) participated in this study. They provided demographic data, along with breast milk and urine samples. OTA levels were measured by a competitive enzyme-linked immunosorbent assay (ELISA) with a detection limit of 60 ng/L for milk and 30 ng/L for urine. OTA was detected in 62.2% of all breast milk samples (mean 74.8 ± 49.0 ng/L, range < LOD–243.3 ng/L) and in 51.4% of all urine samples (mean 44.3 ± 63.5 ng/L, range < LOD–519.3 ng/L). The differences observed between regions for mean breast milk or for urinary OTA levels were relatively small. No significant correlation was observed between OTA levels in breast milk and food consumption patterns among nursing mothers. Regarding infant exposure, the estimated average daily intake of OTA for all was 15.0 ng/kg bw/day (range 4.5–45 ng/kg bw/day). In 34.5% of these infants, their estimated daily OTA intake exceeded a preliminary TDI value set by EFSA (17 ng/kg bw/day). The mean OTA intake was slightly higher (16.2 ± 7.8 ng/kg bw/day) in 1–2 months babies than in older infants (< 2 to 12 months), although the difference was not significant. Presence of OTA in most milk and urine samples of nursing mothers documents their widespread dietary mycotoxin exposure. Although based on a relatively small number of participants, the present analysis indicates non-negligible exposure of some nursed infants in Bangladesh. Therefore, further biomonitoring studies and investigations on major sources of OTA in food commodities are encouraged.

Formulation of Moringa oleifera nanobiopesticides and their evaluation against Tribolium castaneum and Rhyzopertha dominica - Humaira Iqbal; Nazish Jahan; Shaukat Ali; Aamir Shahzad; Rashda Iqbal (Journal of Plant Diseases and Protection, 2024)

Composition and relative abundance of plastic debris along Manora and Sandspit beaches, Karachi, Pakistan - Bakhtawar Suhail; Humaira Kanwal; Muhammad Arsalan (Journal of Coastal Conservation, 2024)

Development of reverse transcription loop-mediated isothermal amplification (RT-LAMP) for rapid detection of viruses infecting patchouli (Pogostemon cablin) - Humaira Bano; Jawaid A. Khan (Archives of Microbiology, 2024)

Physicochemical and sweetness behavior of kosmotropic and chaotropic ions in aqueous solutions of polyhydroxy compound - Uzma Shahazidy; Muhammad Asghar Jamal; Bushra Naseem; Humaira Asghar (Food Chemistry, 2024)

Green synthesized silver nanoparticles: Characterization, phytostimulatory impacts, and degradation potential for organic pollutants - Ghania Abbas; Fozia Batool; Ambreen Ahmed; Shabana Wagi; Humaira Yasmeen Gondal; Farah Maqsood; Ehab A. Abdelrahman; Hafiza Komal Naeem; Samia Kanwal; Muhammad Mustaqeem; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

FlowDyn: A daily streamflow prediction pipeline for dynamical deep neural network applications - S. Sadeghi Tabas; N. Humaira; S. Samadi; N.C. Hubig (Environmental Modelling & Software, 2023)

Exogenous melatonin mitigates the adverse effects of drought stress in strawberry by upregulating the antioxidant defense system - Muhammad Qaisar Naeem Khan; Nevzat Sevgin; Humaira Rizwana; Nida Arif (South African Journal of Botany, 2023)

Mitigation of the Deleterious Effect of Heavy Metals on the Conformational Stability of Ubiquitin through Osmoprotectants - Khadega Khamis Moh Alazoumi; Pradakshina Sharma; Asimul Islam; Humaira Farooqi (Cell Biochemistry and Biophysics, 2023)

Nano priming for boosting growth and resilience in crops under abiotic stresses - Faizan Khalid; Kanza Asif; Yumna Rasheed; Humaira Ashraf; Muhammad Faisal Maqsood; Shamsa Rana; Usman Zulfiqar; Nargis Naz; Muhammad Shahbaz; Rehana Sardar; Zunaira Riaz (Biocatalysis and Agricultural Biotechnology, 2023)

Modeling the nexus of data analytics, sustainability practices and quality management: Evidence of key enablers - Sayem Ahmed; Tazim Ahmed; Humaira Nafisa Ahmed; Syed Mithun Ali; Ernesto D. R. Santibanez Gonzalez; Golam Kabir (Environment, Development and Sustainability, 2023)

Effect of heterologous platelet-rich plasma on liver and modulation of glucose metabolism and Wnt signalling pathways in diabetic mice - Amin Arif; Adil Farooq; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Tasleem Akhtar; Humaira Allay Ali; Mehreen Anjum; Rabia Mehmood; Tayyaba Saleem; Nadeem Sheikh (Molecular Biology Reports, 2023)

Isolation of Endophytic Fungi from Halophytic Plants and their Identification and Screening for Auxin Production and Other Plant Growth Promoting Traits - Muhammad Ikram; Niaz Ali; Gul Jan; Farzana Gul Jan; Rainaz Pervez; Muhammad Romman; Rimsha Zainab; Humaira Yasmin; Naeem Khan (Journal of Plant Growth Regulation, 2023)

Exogenous application of sodium hydrosulfide and salicylic acid mitigate salinity stress in maize by regulating ionic balance, biochemical attributes, photosynthetic pigments and some key antioxidants - Sidra Shoukat; Ayesha Tassawar; Rumana Keyani; Mohsin Zafar; Rabia Naz; Asia Nosheen; Zafar Abbas Shah; Prashant Kaushik; Mohammed Nasser Alyemeni; Humaira Yasmin; Parvaiz Ahmad (South African Journal of Botany, 2023)

Inclusiveness in Food Data Sets: Development of a Food Composition Dataset for South Asian Recipes With Focus on Pakistan - Muhammad Hammad Maqdoom; Syeda Areesha Najam; Shalin Ali; Sana Fatima; Alisha Momin; Abdul Samad; Humaira Jamshed (Journal of Nutrition Education and Behavior, 2023)

Environmental sustainability disclosure in Asian countries: Bibliometric and content analysis - Indah Fajarini Sri Wahyuningrum; Natasya Ghinna Humaira; Mochamad Arief Budihardjo; Indah Sekar Arumdani; Annisa Sila Puspita; Adranandini Noor Annisa; Annisa Mayang Sari; Hadrian Geri Djajadikerta (Journal of Cleaner Production, 2023)

Phycoremediation of industrial wastewater using Vaucheria debaryana and Cladophora glomerata - Sara Khan; Amin Ullah; Tehreem Ayaz; Aamir Aziz; Komal Aman; Mudassir Habib; Semih Yilmaz; Arshad Farid; Humaira Yasmin; Qurban Ali (Environmental Monitoring and Assessment, 2023)

Abundance, characteristics, and ecological risks of microplastics in the riverbed sediments around Dhaka city - Md. Saiful Islam; Md. Rezaul Karim; Md Tanvirul Islam; Humaira Tasnim Oishi; Zarin Tasnim; Harinarayan Das; A. H. M. Enamul Kabir; Masahiko Sekine (Science of The Total Environment, 2023)

Genetic analysis of ACE2 peptidase domain in SARS-CoV-2-positive and SARS-CoV-2-negative individuals from Pakistan - Noor Muhammad; Humaira Naeemi; Ayesha Azeem; Rida Sadaqat; Umara Shehzad; Kashif Siddique; Usman Hassan; Aun Raza; Muhammad Usman Rashid (Molecular Biology Reports, 2023)

Design and application of chitosan-CuO nanocomposites synthesized via novel hybrid ionic gelation-ultrasonication methods for water disinfection - Fitri Khoerunnisa; Mita Nurhayati; Humaira Herlini; Qurratu Aini Alya Adzkia; Fitri Dara; Hendrawan Hendrawan; Wen-Da Oh; JitKang Lim (Journal of Water Process Engineering, 2023)

Photocatalytic and Antibacterial Potential of Silver Nanocubes and Nanorods Synthesized via Polyol Reduction Method - Muhammad Zahid Ishaque; Yasir Zaman; Muhammad Shahzad; Abu Bakar Siddique; Sana Shahid; Muhammad Akram; Humaira Kanwal; Muhammad Tahir Akhtar; Safdar Hussain (Water, Air, & Soil Pollution, 2023)

RETRACTED ARTICLE: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Engineering nanocomposite membranes of sodium alginate-graphene oxide for efficient separation of oil-water and antifouling performance - Mehwish Ehsan; Humaira Razzaq; Shumaila Razzaque; Memoona Kanwal; Irshad Hussain (Journal of Environmental Chemical Engineering, 2023)

Polymeric Nanogel for Oral Delivery of the Chemotherapeutic Agent: Fabrication and Evaluation Alongside Toxicological Studies and Histopathological Examination - Humaira Sultana; Muhammad Naeem Aamir; Asadullah Madni; Masood ur Rehman; Afifa Shafiq; Jafir Hussain Shirazi; Sidra Hassan; Sumaira (AAPS PharmSciTech, 2023)

Fintech development, renewable energy consumption, government effectiveness and management of natural resources along the belt and road countries - Qingmei Tan; Humaira Yasmeen; Sharafat Ali; Hina Ismail; Hashim Zameer (Resources Policy, 2023)

Zinc oxide nanoparticles mediated biostimulant impact on cadmium detoxification and in silico analysis of zinc oxide-cadmium networks in Zea mays L. regulome - Yashfa Tanveer; Saman Jahangir; Zafar Abbas Shah; Humaira Yasmin; Asia Nosheen; Muhammad Nadeem Hassan; Noshin Illyas; Andrzej Bajguz; Mohamed A. El-Sheikh; Parvaiz Ahmad (Environmental Pollution, 2023)

Insight into microwave-assisted synthesis of the chitosan-MOF composite: Pb(II) adsorption - Humaira Gul Zaman; Lavania Baloo; Shamsul Rahman Kutty; Khalid Aziz; Muhammad Altaf; Aniqa Ashraf; Faissal Aziz (Environmental Science and Pollution Research, 2023)

Measurement and comparison of photosynthetically active radiation by different methods at Delhi - Humaira Ghayas; S. R. Radhakrishnan; Vinay Kumar Sehgal; Sachchidanand Singh (Theoretical and Applied Climatology, 2022)

Flooding tolerance in plants: from physiological and molecular perspectives - Nasrullah; Shahid Ali; Muhammad Umar; Lifang Sun; Muhammad Naeem; Humaira Yasmin; Naeem Khan (Brazilian Journal of Botany, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Wildlife habitat-suitability analysis for high mountain national parks in the Hindu Kush, Karakoram and Himalayan region of northern Pakistan - Siddique Ullah Baig; Adeel Jalal Malik; Humaira Khan (Modeling Earth Systems and Environment, 2022)

Spatial evaluation of precipitation patterns in the catchment area of Malir River during monsoon spells of 2019 through geospatial techniques - Syed Wasi Haider; Syed Jamil Hasan Kazmi; Muhammad Arsalan; Shahid Naseem; Humaira Kanwal (Arabian Journal of Geosciences, 2022)

Lethal and sublethal effects of flonicamid (50 WG) and spirotetramat (240 SC) on Bemisia tabaci (Homoptera: Aleyrodidae): an age-stage two sex life table study - Aqsa Abbas; Javaid Iqbal; Ali Zeshan; Qurban Ali; Imran Nadeem; Humaira Malik; Tamsila Nazir; Muhammad Faheem Akhter; Bilal Bin Iqbal (Phytoparasitica, 2022)

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

Prospect of Anterior Gradient 2 homodimer inhibition via repurposing FDA-approved drugs using structure-based virtual screening - Shafi Ullah; Shafi Ullah Khan; Abbas Khan; Muhammad Junaid; Humaira Rafiq; Thet Thet Htar; Yaxue Zhao; Syed Adnan Ali Shah; Abdul Wadood (Molecular Diversity, 2022)

Choline Chloride Mediates Chromium Tolerance in Spinach (Spinacia oleracea L.) by Restricting its Uptake in Relation to Morpho-physio-biochemical Attributes - Iqbal Hussain; Muhammad Hamzah Saleem; Sahar Mumtaz; Rizwan Rasheed; Muhammad Arslan Ashraf; Faisal Maqsood; Muzammal Rehman; Humaira Yasmin; Shakeel Ahmed; Muhammad Ishtiaq; Sana Anwar; Shafaqat Ali (Journal of Plant Growth Regulation, 2022)

Drought-tolerant Bacillus megaterium isolated from semi-arid conditions induces systemic tolerance of wheat under drought conditions - Urooj Rashid; Humaira Yasmin; Muhammad Nadeem Hassan; Rabia Naz; Asia Nosheen; Muhammad Sajjad; Noshin Ilyas; Rumana Keyani; Zahra Jabeen; Saqib Mumtaz; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Plant Cell Reports, 2022)

Genetic predisposition of SNPs in miRNA-149 (rs2292832) and FOXE1 (rs3758249) in thyroid Cancer - Rashida Khan; Humaira Shaheen; Qaisar Mansoor; Samina Asghar Abbasi; Shazia Fatima; Ayesha Ammar; Ruqia Mehmood Baig (Molecular Biology Reports, 2021)

Subtractive Proteomics and Immuno-informatics Approaches for Multi-peptide Vaccine Prediction Against Klebsiella oxytoca and Validation Through In Silico Expression - Qudsia Yousafi; Humaira Amin; Shabana Bibi; Rafea Rafi; Muhammad S. Khan; Hamza Ali; Ashir Masroor (International Journal of Peptide Research and Therapeutics, 2021)

Assessing Pakistan’s energy use, environmental degradation, and economic progress based on Tapio decoupling model - Humaira Yasmeen; Qingmei Tan (Environmental Science and Pollution Research, 2021)

Morpho-physiological investigations in transgenic tomato (Solanum lycopersicum L.) over expressing OsRGLP1 gene - Sumera Perveen; Tehmina Ahsan Khan; Humaira Shaheen; Rabia Naz; Muhammad Zeeshan Hyder; Bushra Ijaz; S. M. Saqlan Naqvi; Tayyaba Yasmin (In Vitro Cellular & Developmental Biology - Plant, 2021)

Infiltration in vegetated soil: empirical modeling and sensitivity analysis - Md. Enayet Chowdhury; Mohammad Shariful Islam; Tahsina Alam; Sagar Barua; Md. Safin Shahriar; Humaira Anisa (Modeling Earth Systems and Environment, 2021)

Hippophae rhamnoides mediate gene expression profiles against keratinocytes infection of Staphylococcus aureus - Humaira Shah; Hafiz Abdullah Shakir; Sher Zaman Safi; Abid Ali (Molecular Biology Reports, 2021)

Molecular characterization and insights into the origin of common bean (Phaseolus vulgaris L.) landraces of north western Himalayas - Humaira Bashir; Zafar Bashir; Reetika Mahajan; Muslima Nazir; Rakeeb A. Mir; F. A. Nehvi; Sajad Majeed Zargar (The Nucleus, 2020)

Mechanistic Approaches of Internalization, Subcellular Trafficking, and Cytotoxicity of Nanoparticles for Targeting the Small Intestine - Asadullah Madni; Sadia Rehman; Humaira Sultan; Muhammad Muzamil Khan; Faiz Ahmad; M. Rafi Raza; Nadia Rai; Farzana Parveen (AAPS PharmSciTech, 2020)

Targeting glutathione with the triterpenoid CDDO-Im protects against benzo-a-pyrene-1,6-quinone-induced cytotoxicity in endothelial cells - Halley Shukla; Ho Young Lee; Ashkon Koucheki; Humaira A. Bibi; Gabriella Gaje; Xiaolun Sun; Hong Zhu; Y. Robert Li; Zhenquan Jia (Molecular and Cellular Biochemistry, 2020)

Hydrogeochemical investigation of arsenic in drinking water of schools and age dependent risk assessment in Vehari District, Punjab Pakistan: a multivariate analysis - Behzad Murtaza; Humaira Nazeer; Natasha; Muhammad Amjad; Muhammad Imran; Muhammad Shahid; Noor S. Shah; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Murtaza (Environmental Science and Pollution Research, 2020)

Analyzing the association between innovation, economic growth, and environment: divulging the importance of FDI and trade openness in India - Hashim Zameer; Humaira Yasmeen; Muhammad Wasif Zafar; Abdul Waheed; Avik Sinha (Environmental Science and Pollution Research, 2020)

Biodiversity conservation in the Hindu Kush-Karakoram-Himalayan mountain region of northern Pakistan: Overview of big mammal protection - Humaira Khan; Siddique Ullah Baig (Journal of Mountain Science, 2020)

Nucleophilic phenylation: a remarkable application of alkoxymethyltriphenylphosphonium salts - Zain Maqsood Cheema; Humaira Yasmeen Gondal; Abdul Rauf Raza; Ahmed Abbaskhan (Molecular Diversity, 2020)

Exogenously applied 5-aminolevulinic acid modulates growth, secondary metabolism and oxidative defense in sunflower under water deficit stress - Rizwan Rasheed; Humaira Yasmeen; Iqbal Hussain; Muhammad Iqbal; Muhammad Arslan Ashraf; Abida Parveen (Physiology and Molecular Biology of Plants, 2020)

Effects of early rearing enrichments on modulation of brain monoamines and hypothalamic–pituitary–interrenal axis (HPI axis) of fish mahseer (Tor putitora) - Imdad Ullah; Amina Zuberi; Humaira Rehman; Zulfiqar Ali; Per-Ove Thörnqvist; Svante Winberg (Fish Physiology and Biochemistry, 2020)

Decomposing factors affecting CO2 emissions in Pakistan: insights from LMDI decomposition approach - Humaira Yasmeen; Ying Wang; Hashim Zameer; Yasir Ahmed Solangi (Environmental Science and Pollution Research, 2020)

Correction to: Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Phenotypic and molecular characterization of diazotrophic bacteria associated with sugarcane in Bangladesh - Imam Taskin Alam; Syeda Roufun Nesa; Khandakar Mohiul Alam; Anowara Begum; Humaira Akhter (Organic Agriculture, 2019)

Identification and characterization of dwarf mistletoe responding genes in Ziarat juniper tree (Juniperus excelsa M.Bieb) through suppression subtractive hybridization and deep sequencing - Humaira Abdul Wahid; Muhammad Younas Khan Barozai; Muhammad Din (Trees, 2019)

Polyphenolic profiling of Ipomoea carnea Jacq. by HPLC-DAD and its implications in oxidative stress and cancer - Muhammad Zafar Irshad Khan; Syeda Saniya Zahra; Madiha Ahmed; Humaira Fatima; Bushra Mirza; Ihsan-ul Haq; Shafi Ullah Khan (Natural Product Research, 2019)

Glucanolytic Rhizobacteria Produce Antifungal Metabolites and Elicit ROS Scavenging System in Sugarcane - Muhammad Atif Zia; Humaira Yasmin; Faluk Shair; Zahra Jabeen; Saqib Mumtaz; Zafar Hayat; Syed Zia ul Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (Sugar Tech, 2019)

Heavy metal contamination in two commercial fish species of a trans-Himalayan freshwater ecosystem - Mohammad Aneesul Mehmood; Humaira Qadri; Rouf Ahmad Bhat; Asmat Rashid; Sartaj Ahmad Ganie; Gowhar Hamid Dar; Shafiq-ur-Rehman (Environmental Monitoring and Assessment, 2019)

Environmental and socioeconomic factors induced blood lead in children: an investigation from Kashmir, India - Asmat Rashid; Rouf Ahmad Bhat; Humaira Qadri; Mohammad Aneesul Mehmood; Shafiq-ur-Rehman (Environmental Monitoring and Assessment, 2019)

Plant growth promoting endophytic fungi Asprgillus fumigatus TS1 and Fusarium proliferatum BRL1 produce gibberellins and regulates plant endogenous hormones - Lubna Bilal; Sajjad Asaf; Muhammad Hamayun; Humaira Gul; Amjad Iqbal; Ihsan Ullah; In-Jung Lee; Anwar Hussain (Symbiosis, 2018)

Hypsometric properties of mountain landscape of Hunza River Basin of the Karakoram Himalaya - Siddique Ullah Baig; Adnan Ahmad Tahir; Ahmad Din; Humaira Khan (Journal of Mountain Science, 2018)

Correction to: Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Distribution of IL28B and IL10 polymorphisms as genetic predictors of treatment response in Pakistani HCV genotype 3 patients - Humaira Naeemi; Rabia Aslam; Syed Mohsin Raza; Muhammad Aiman Shahzad; Shagufta Naz; Sobia Manzoor; Saba Khaliq (Archives of Virology, 2018)

4-quinolin-8-yloxy Linked Triphenylamine Based Polyimides: Blue Light Emissive and Potential Hole-Transport Materials - Asma Iqbal; Naila Khalid; Humaira M. Siddiqi; O. Ok Park; Toheed Akhter (Journal of Fluorescence, 2018)

Synthesis and Photophysical Study of New Green Fluorescent TPA Based Poly(azomethine)s - Naila Khalid; Asma Iqbal; Humaira Masood Siddiqi; O. Ok Park (Journal of Fluorescence, 2017)

Characterization and Fine Mapping of SFL1, a Gene Controlling Screw Flag Leaf in Rice - Md. Alamin; Dong-Dong Zeng; Ran Qin; Most. Humaira Sultana; Xiao-Li Jin; Chun-Hai Shi (Plant Molecular Biology Reporter, 2017)

High Altitude Wetlands of the HKH Region of Northern Pakistan – Status of Current Knowledge, Challenges and Research Opportunities - Humaira Khan; Siddique Baig (Wetlands, 2017)

SSR based genetic diversity of pigmented and aromatic rice (Oryza sativa L.) genotypes of the western Himalayan region of India - Humaira Ashraf; Amjad M. Husaini; M. Ashraf Bhat; GA Parray; Salim Khan; Nazir A. Ganai (Physiology and Molecular Biology of Plants, 2016)

In silico transcriptional regulation and functional analysis of dengue shock syndrome associated SNPs in PLCE1 and MICB genes - Malik Mumtaz Taqi; Durdana Waseem; Humaira Ismatullah; Syed Aleem Haider; Muhammad Faisal (Functional & Integrative Genomics, 2016)

Design, optimization, and evaluation of ezetimibe solid supersaturatable self-nanoemulsifying drug delivery for enhanced solubility and dissolution - Rajendra Narayan Dash; Habibuddin Mohammed; Touseef Humaira (Journal of Pharmaceutical Investigation, 2016)

Petrogenetic evolution of pegmatites of the Shigar Valley, Skardu, Gilgit-Baltistan, Pakistan - Muhammad Hassan Agheem; Mohammad Tahir Shah; Tahseenullah Khan; Mamoru Murata; Humaira Dars; Muhammad Zafar (Arabian Journal of Geosciences, 2015)

Hydrological response to environment change in Himalayan watersheds: Assessment from integrated modeling approach - Zulfiqar Ahmad; Arshad Ashraf; Muhammad Zaheer; Humaira Bashir (Journal of Mountain Science, 2015)

Shigar valley gemstones, their chemical composition and origin, Skardu, Gilgit-Baltistan, Pakistan - Muhammad Hassan Agheem; Mohammad Tahir Shah; Tahseenullah Khan; Mamoru Murata; Muhammad Arif; Humaira Dars (Arabian Journal of Geosciences, 2014)

Influence of urea fertiliser formulation, urease inhibitor and season on ammonia loss from ryegrass - Helen Suter; Humaira Sultana; Debra Turner; Rohan Davies; Charlie Walker; Deli Chen (Nutrient Cycling in Agroecosystems, 2013)

Determination of cadmium and zinc in vegetables with online FAAS after simultaneous pre-concentration with 1,5-diphenylthiocarbazone immobilised on naphthalene - Zaheer A. Chandio; Farah N. Talpur; Humaira Khan; H.I. Afridi; Ghulam Quadir Khaskheli (Food Additives & Contaminants: Part A, 2013)

Serum Magnesium and Atherogenic Lipid Fractions in Type II Diabetic Patients of Lahore, Pakistan - Humaira Rasheed; Shan Elahi; Humayun Ajaz (Biological Trace Element Research, 2012)

Lead (Pb)-Induced Regulation of Growth, Photosynthesis, and Mineral Nutrition in Maize (Zea mays L.) Plants at Early Growth Stages - Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Qaisra Tabassam; Mumtaz Hussain; Humaira Firdous (Biological Trace Element Research, 2011)

Quantification of the spatiotemporal microstructural organization of the human brain association, projection and commissural pathways across the lifespan using diffusion tensor tractography - Khader M. Hasan; Arash Kamali; Humaira Abid; Larry A. Kramer; Jack M. Fletcher; Linda Ewing-Cobbs (Brain Structure and Function, 2010)

Hepatitis C therapy—the future looks bright - Sohail A. Qureshi; Humaira Qureshi; Anam Hameed (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Vulnerability and adaptability of wheat production in different climatic zones of Pakistan under climate change scenarios - Humaira Sultana; Nazim Ali; M. Mohsin Iqbal; Arshad M. Khan (Climatic Change, 2009)

Sclareol induces apoptosis in human HCT116 colon cancer cells in vitro and suppression of HCT116 tumor growth in immunodeficient mice - Konstantinos Dimas; Sophia Hatziantoniou; Sophia Tseleni; Humaira Khan; Aristidis Georgopoulos; Konstantinos Alevizopoulos; James H. Wyche; Panayotis Pantazis; Costas Demetzos (Apoptosis, 2007)

Hydrogeomorphic (HGM) assessment—A test of user consistency - Dennis F. Whigham; Lyndon C. Lee; Mark M. Brinson; Richard D. Rheinhardt; Mark C. Rains; Jeffrey A. Mason; Humaira Kahn; Melanie B. Ruhlman; Wade L. Nutter (Wetlands, 1999)